(untitled) (Open Herald: Periodical of Methodical Research, 2025)
This article explores the linguacultural features of godonims (a subgroup of toponyms) in the Uzbek and English languages. Godonims, which refer to place names rooted in local traditions, historical events, or cultural significance, reflect the values, beliefs, and worldviews of the societies that create them. This study compares godonims in Uzbek and English, examining their linguistic structures, meanings, and the cultural elements they embody. The analysis focuses on how these place names are used to convey the identity of the geographic regions and societies they represent. The research highlights both the commonalities and differences between Uzbek and English godonims, exploring their role in cultural expression and the preservation of historical heritage. The study uses a qualitative approach, analyzing a variety of godonims in both languages